Potential Function of Microbial Mats in Regard to Water Chemistry and Carbonate Precipitation in the Alkaline Waterbody Lake Van (Turkey) - Cangemi, Marianna; Oliveri, Ygor; Sasmaz, Bilge; Censi, Paolo; Sasmaz, Ahmet (Mdpi, 2025)
In this article, we examine water chemistry and carbonate precipitation in the alkaline waterbody Lake Van in Turkey, analyzing the possible role of microbial communities in stromatolite formation. Lake Van represents a unique environment characterized by high salinity and pH and extensive microbial communities, as revealed by SEM observation. Microbial activity, including that of cyanobacteria, can influence carbonate precipitation processes, leading to the formation of authigenic carbonates through physicochemical or metabolic mechanisms such as photosynthesis or sulfate reduction. In these environments, which are often dominated by cyanobacteria, carbonate precipitation can be influenced by biologically induced processes. This study presents new data on the hydrochemistry of lake water, focusing on the behavior of rare-earth elements (REEs) in this water and the carbon and oxygen isotopic compositions of carbonate microbial mats. The oxygen isotope data suggest that inorganic carbonate precipitation is the dominant process, but a biological influence on inorganic precipitation cannot be ruled out. For a deeper understanding of the role of biological processes in Lake Van, further studies on microbialites are needed.
Keywords: alkaline lake; microbialites; isotopic composition; rare earth elements